THE ROLE OF CLASSROOM INTERACTION IN SECOND LANGUAGE ACQUISITION IN SRI LANKA - Perera, M.E.S. (My University, 2001)
The objective of teaching English as a second language in the secondary schools in Sri Lanka is for oral communication. Between 1985 to 1999, the English Every Day (EED) learning materials were used in all Sri Lankan schools. These materials were informed by Communicative Language Teaching (CLT), which advocates oral interaction. The available literature suggests that the teaching of English in Sri Lanka is not satisfactory and does not meet the needs of the majority of Sri Lankan students. Attempts have been made to find ways of improving the teaching of English by changing the curriculum regularly, yet very few classroom based studies have been conducted. The reasons for very little success in the teaching of English could be in part due to trying to find the best method to teach English rather than identifying the problems faced in learning English in the classroom. The purpose of this study was to investigate the role of classroom interaction in second language acquisition in Sri Lanka. The study was guided by two main research questions. The first asked how the relationship between the teacher, the students and the learning materials provided opportunities for second language learning in selected second language classrooms; and the second how the teacher-pupil oral interactions in the classrooms promoted possibilities for second language development. These questions were examined in relation to four schools selected from diverse socio-cultural backgrounds, using a predominantly ethnographic approach based on observational case studies. However, as the learning materials used in the classrooms were based on CLT, a more focused approach drawing on CLT and Second Language Acquisition theories specific to oral interaction was used to complement the qualitative data collected for each case. The selection of the four schools from diverse backgrounds permitted comparisons across the cases. In each school the main data gathering techniques were audio recordings of oral interactions and field notes. Open ended interviews with teachers, the collection of documentation such as student learning materials, lesson notes and teacher record books were used as supplementary data. The socio-cultural and political influences on the historical development of English as a second language in Sri Lanka were investigated in order to understand the context in which English is taught. The learning materials used in the classrooms were analysed in relation to CLT principles to identify the teaching methodology used in the classrooms and the potential areas of difficulties for teachers in promoting second language development in the classroom. The transcripts of recorded teacher-pupil interactions, interview data and field notes were analysed to examine how the classroom practices exemplify the principles on which the learning materials are based and the opportunities provided in each classroom for second language learning. The findings of the study indicate that the interactions observed in the classrooms were the outcomes of a complex relationship between a heterogeneous group of students, their teachers who differed in terms of their experiences and preparation for teaching English, and the EED learning materials. The purpose for which the students learned English differed across schools, as well as between students, and was related to the culture of the school and the students’ socio-economic background. In addition, there was a mismatch between the recommended process-oriented teaching approach in the learning materials and the Sri Lankan product-based examination system. As a result of these complex factors, which are also related to the socio-cultural and political context in Sri Lanka, the opportunities provided for second language development were different in each of the observed classrooms in this study. The findings in this study challenge the assumption in Sri Lanka that equal opportunities to learn English can be provided simply by using the same learning materials, based on the same teaching approach with all the students. These findings suggest the need for more classroom based ethnographic research to understand the complex factors affecting the teaching of English and to inform teacher education programs. It also underscores the differences between ESL classrooms across cultures and within cultures and the danger of advocating classroom practices as effective in all contexts.